Оптимизация хирургического лечения больных с лучевыми повреждениями покровных тканей = Features of surgical treatment of radiation damage of superficial tissues = Оптимізація хірургічного лікування променевих пошкоджень покривних тканин - Goni, S. A. T. (Journal of Education, Health and Sport, 2016)
Goni S.-A. T. Оптимизация хирургического лечения больных с лучевыми повреждениями покровных тканей = Features of surgical treatment of radiation damage of superficial tissues = Оптимізація хірургічного лікування променевих пошкоджень покривних тканин Journal of Education, Health and Sport. 2016;6(10):501-509. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.165848 http://ojs.ukw.edu.pl/index.php/johs/article/view/3984 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. Оптимизация хирургического лечения больных с лучевыми повреждениями покровных тканей С. А. Т. Гони Харьковский национальный медицинский университет МОЗ Украины, кафедра хирургии №2 Резюме Представлен анализ результатов лечения 29 больных поздними лучевыми повреждениями покровных тканей. Изучена эффективность различных видов кожной пластики при различных локализациях лучевых язв. Больные, получившие оперативное лечение (n=10) были разделены по типу пластики на две группы: пластика местными тканями (3 больных, 30%), и пластика кожным лоскутом: свободная кожная пластика (2 больных, 20%) и кожная пластика полнослойным лоскутом с осевым кровообращением (5 больных, 50%). Локализация лучевых язв – грудная клетка, голова, голень и крестцовая область. Размеры язв колебались от 2 до9 см. Ключевые слова: поздняя лучевая язва, кожная пластика, определение жизнеспособности ткани Features of surgical treatment of radiation damage of superficial tissues S. A. T. Goni Kharkiv National Medical University, Ministry of Health of Ukraine , Department of Surgery № 2 Summary Presents an analysis of the results of treatment of 29 patients with late radiation damage of superficial tissues. Studied the effectiveness of different types of skin plastics at different locations of radiation ulcers. Operated patients were divided by the type of plastic: plastic with local tissues (3 patients, 30%), free dermepenthesis (2 patients, 20%) and unfree dermepenthesis (5 patients, 50%). Localization of radiation ulcers - chest, anterior abdominal wall, lumbar and sacral area. Size of the ulcers ranged from 2 to9 cm Keywords : late radiation ulcers, skin plastic, determining tissue viability, PDT, plasmotherapy